Conditional Cash Transfers: The Case ofProgresa/Oportunidades - Parker, Susan W.; Todd, Petra E. (Journal of Economic Literature, 2017)
Conditional cash transfer (CCT) programs innovate by conditioning transfers to poor families on investments in the human capital of children and other family members. The Mexican CCT program Progresa/Oportunidades began in 1997 and has served as a model for many of the now over sixty countries with CCTs around the world, in large part due to its initial evaluation with an experimental design and numerous follow-up studies. This article reviews the literature on the development, evaluation, and findings of Progresa/Oportunidades, summarizing what is known about program effects, taking into account corrections for multiple-hypothesis testing. ( JEL H23, I18, I28, I32, I38, O15)